The case study of 30 years UiTM Pahang's development as a sustainable university campus / Mohd. Mawardi Mohd Kamal, Normadiana Mohammad Hanapi and Mohd Ikhsan Md Raus - Mohd Kamal, Mohd. Mawardi; Mohammad Hanapi, Normadiana; Md Raus, Mohd Ikhsan (2015)
On 22 August 1988, Universiti Teknologi MARA (UiTM) Pahang was announced to be a permanent campus for ITM Cawangan Pahang by the Menteri Besar, Y.B. Dato Seri Haji Khalil Yaakob. The state government of Pahang had allocated 1000 acres of land in Bandar Pusat Jengka, in the Maran district, to be the site for the permanent campus to be built. The process in building the campus involved two phases, the initial phase to accommodate 2500 students and eventually the campus, with its full facilities and infrastructure, to be able to accommodate 4500 students. Recently, UiTM Pahang has achieved its 30 years of the development in the academic as well as in providing facilities and infrastructures. This study focuses on the development of facilities and infrastructures of UiTM Pahang as a sustainable campus. Based on the location of UiTM, the campus is portrayed by the sustainability with the nature as it is located in the agricultural area. The aim of this research is to study the construction in UiTM for 30 years in order to conclude that UiTM Pahang can be considered as a Sustainable University Campus. This is very important for the future as UiTM Pahang should be the first University that applied the sustainable development, which is a process for meeting our development goals while sustaining the ability of natural systems to continue to provide the natural resources and ecosystem services upon which the economy and society depend.